Verslo ir informacinių technologijų darna - Paškevičiūtė, Lina; Čaplinskas, Albertas (Information & Media, 2008)
Informacinių technologijų vaidmuo šiandienėje įmonėje yra itin svarbus. Neužtikrinus tinkamo sąryšio tarp informacinių technologijų ir veiklos, šios technologijos gali būti naudojamos neveiksmingai ar netgi nuostolingai. Straipsnyje analizuojamos verslo ir informacinių technologijų atotrūkio priežastys ir padariniai, lyginamos skirtingos verslo ir informacinių technologijų darnos sampratos*.Business and information technology alignmentLina Paškevičiūtė, Albertas ČaplinskasSummaryInformation technology (IT) plays a very important role in nowadays business. The usage of IT may not increase the efficiency of business activities and may even result in huge financial losses if the IT and business are not properly aligned. In this paper, the results of analysis of possible influences of gaps between business and IT are presented. A comparison of a number of different definitions and interpretations of IT-business alignment concept is also presented.